The role of TCR-z expression in immunosuppression induced by tumour - Sikora, Jan (Contemporary Oncology/Współczesna Onkologia, 2009)
The z-chain is a 16-kDa molecule associated with the T-cell receptor TCR-CD3 complex in T lymphocytes and FcgRIII in NK cells. The z functions as a transmembrane signaling molecule. Several distinct mechanisms may be responsible for decreased/absent z in T cells of patients with cancer. Assessment of z-chain expression in the course of various diseases shows changes in expression of this molecule in immune cells. Immunohistochemical evaluation of z expression can link it to the conventional markers of prognosis or survival. Monitoring for z expression is useful for assessing immune competence in these patients and for following changes in immune competence during anticancer therapies. Correlations made between clinical findings, pathologic results, and z expression in immune cells suggest that low/absent z is predictive of poor prognosis and survival in patients with cancer.